The carnival directorial image and its representations in the contemporary Iraqi theatrical show. (Othello in the kitchen) An example. (Al-Academy, 2024)
The tagged research dealt with (the preoccupations of the carnival image in contemporary theater performances) four chapters, in the first chapter dealt with the methodological framework, including the research problem (what is the carnival directorial image in the contemporary Iraqi theatrical show) (Othello in the Kitchen) as a model? The importance of the research came with three axis as follows : The first axis is shedding light on the concept of the carnival in contemporary theatrical performance, As for the second ; the research seeks to clarify the effects of the concept of the carnival on the discourse of theatrical performance and to identify the artistic and aesthetic treatments in the directorial features of the theatrical performance, in the final axis the research seeks to shed light on the representations of the carnival in the performance of the play (Othello in the Kitchen) and the aim of the research (how does the carnival image work in the performance of the play (Othello in the Kitchen)? While the temporal limits of the research were 1995. The second chapter dealt with the theoretical framework, including two topics; The first topic was (conceptually and philosophically carnival) and the second topic (the preoccupations of the carnival image in the theatrical performance) and then the indicators of what resulted in the theoretical framework. Then the third chapter dealt with the research sample of play (Othello play in the kitchen), and the fourth chapter dealt with the research results and conclusions